Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan Pada PT Bumi Siak Pusako (PT. BSP) - Febriani Febriani; Okta Karneli (Komunitas Dosen Indonesia, 2025)
This study aims to understand the extent to which compensation and work environment affect employee productivity at PT Bumi Siak Pusako (PT BSP). This is relevant because in the era of globalization, fierce business competition requires companies to focus more on increasing employee productivity as one of the key factors to achieve company sustainability and growth. The decline in the productivity of PT BSP employees in recent years has raised concerns, where productivity decreased from 102% in 2019 to 86% in 2023. Most likely, this is due to delays in providing compensation and inadequate working environment conditions. A quantitative approach was used by a survey method of 73 operational employees as respondents. Analysis technique with multiple linear regression. The findings found that compensation and the work environment significantly had a positive impact on work productivity. Of the two variables, compensation has a more dominant influence than the work environment. PT BSP needed to improve the compensation system by ensuring that it was timely and in accordance with the workload. Improving the quality of the work environment is also needed to create safer and more comfortable conditions for employees. Employee productivity can be increased to support the achievement of the company's targets.